2019
DOI: 10.3389/fpls.2019.00655
|View full text |Cite
|
Sign up to set email alerts
|

Ascophyllum nodosum-Based Biostimulants: Sustainable Applications in Agriculture for the Stimulation of Plant Growth, Stress Tolerance, and Disease Management

Abstract: Abiotic and biotic stresses limit the growth and productivity of plants. In the current global scenario, in order to meet the requirements of the ever-increasing world population, chemical pesticides and synthetic fertilizers are used to boost agricultural production. These harmful chemicals pose a serious threat to the health of humans, animals, plants, and the entire biosphere. To minimize the agricultural chemical footprint, extracts of Ascophyllum nodosum (ANE) have been explored for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
296
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(313 citation statements)
references
References 236 publications
(406 reference statements)
5
296
1
11
Order By: Relevance
“…More importantly, depending on the extraction process, the yield of bioactive compounds fluctuates significantly. For instance, extract obtained through water or acid hydrolysis are reported to be rich in phytohormones [18], although such trait may also be inconsistent. Indeed, the previous findings of Ertani et al [19] revealed notable variation of indole acetic acid (IAA) and gibberellic acid (GA) content of five commercial Ascophyllum nodosum-based biostimulants produced via acid extraction, which was plausibly attributed to differences in the sampling zone, timing, and environmental conditions.…”
Section: Manufacturing Process Of Seaweed Extract Biostimulant: the Mmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, depending on the extraction process, the yield of bioactive compounds fluctuates significantly. For instance, extract obtained through water or acid hydrolysis are reported to be rich in phytohormones [18], although such trait may also be inconsistent. Indeed, the previous findings of Ertani et al [19] revealed notable variation of indole acetic acid (IAA) and gibberellic acid (GA) content of five commercial Ascophyllum nodosum-based biostimulants produced via acid extraction, which was plausibly attributed to differences in the sampling zone, timing, and environmental conditions.…”
Section: Manufacturing Process Of Seaweed Extract Biostimulant: the Mmentioning
confidence: 99%
“…As a result, compounds with a biostimulant potential could be lost during this process [20]. Additionally, in alkali extraction, polysaccharide chains are broken down to smaller oligomers, and new compounds not initially present in the algae biomass could be formed [18], which could be advantageous or not as the specific chemical process is not fully controlled. To resolve such issues, the use of UAE could constitute a potential solution.…”
Section: Manufacturing Process Of Seaweed Extract Biostimulant: the Mmentioning
confidence: 99%
“…Polysaccharides, nucleic acids, and peptides are considered the main three types of bioactive polymeric macromolecules [1]. Among these, polysaccharides serve various roles in living cells including structural functions, where cellulose and chitin represent the major components of the different cell wall matrices [2,3], energy storage (e.g., starch and glycogen) [4,5], and hydration and signaling functions (e.g., mucilage and alginic acid) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Seaweeds have been used as fertilizers and soil conditioning agents since ancient times [1,6,7]. The most widely researched seaweed as a plant biostimulant is Ascophyllum nodosum, a marine brown alga, found along the Atlantic coast of North America and Northern Europe [6,8,9]. Ascophyllum nodosum extract (ANE) contains bioactive compounds such as polysaccharides, alginates, vitamins, organic osmolytes, and hormone-stimulating substances that aid in plant growth and establishment [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely researched seaweed as a plant biostimulant is Ascophyllum nodosum, a marine brown alga, found along the Atlantic coast of North America and Northern Europe [6,8,9]. Ascophyllum nodosum extract (ANE) contains bioactive compounds such as polysaccharides, alginates, vitamins, organic osmolytes, and hormone-stimulating substances that aid in plant growth and establishment [9][10][11]. ANE application enhances plant growth and development by increasing seed germination, root and shoot growth, and nutrient uptake [6].…”
Section: Introductionmentioning
confidence: 99%